Investigation of effect of compression ratio on combustion and exhaust emissions in A HCCI engine. (1st February 2019) - Calam, Alper; Solmaz, Hamit; Yılmaz, Emre; İçingür, Yakup
Abstract: In this study effects of compression ratio on HCCI combustion, performance and emissions was investigated parametrically. In addition to parametric investigation and as a novel way of the paper engine BSFC maps were obtained for RON20 andRON40 fuels and each compression ratios of 9:1, 10:1, 11:1 and 12:1. The parametric experiments were carried out at 800 rpm engine speed. In both parametric and mapping experiments were conducted at intake temperature of 353 K. In-cylinder pressure, ROHR, combustion duration, start of combustion, indicated mean effective pressure, thermal efficiency and CO, HC and NOx emissions were examined. It was determined that in-cylinder pressure and rate of heat release decreased while the mixture getting leaner. The increase of octane number of fuel led to extension of combustion duration. On the contrary, combustion duration decreased along with the increase of compression ratio. It was found that the CO and HC emission were high while NOx emissions were low at lower CR. With the increase of CR, CO and HC emissions decreased however NOx emissions increased. The maximum thermal efficiency was obtained as 38.2% at 800 rpm and 12:1 CR with RON40 fuel. The widest operational region was obtained with RON20 fuel at CR of 10:1 with a minimum BSFC value of 210 g/kWh. Highlights: RON20 and RON40 fuels were tested in A HCCI engine at different compression ratios. RON, lambda and compression ratio effects on HCCI engine was examined parametrically. Additionally BSFC and operation maps were determined for each compression ratio. RON40 seems more suitable fuel due to controlling the HCCI combustion in all compression ratios. Largest operation map in terms of engine load and speed was obtained with RON20.